Clinical Implication of Optical Coherence Tomography-Based Neoatherosclerosis - Hong, Sung-Jin; Lee, Seung-Yul; Hong, Myeong-Ki (Journal of Korean medical science, 2017)
Recent research has indicated neoatherosclerosis (NA), the de novo development of atherosclerosis within the neointimal region of the stented segment after coronary stent implantation, as a mechanism of late/very late stent thrombosis (VLST) and restenosis. This research is based on histologic and intravascular imaging studies. Optical coherence tomography (OCT) is an imaging tool that is superior with regard to resolution capacity, and can be used to visualize detailed information about distinct morphological characteristics of the restenotic tissue. Thus, OCT is a valuable imaging tool for examining NA, such as macrophage infiltration, lipid accumulation, in-stent calcification, or neointimal rupture. This article discusses the prevalence, predictors, and clinical implications of NA that can be observed by OCT.